Driving Sustainable Business Performance: The Impact of Green Innovation on Food & Beverage SMEs in Bandar Lampung City - Natalie, Hellen Cornellia; Bangsawan, Satria; Husna, Nurul (International Journal of Business and Applied Economics, 2024)
This research investigates how green innovation, including both product and process innovations, affects the sustainable performance of micro, small, and medium food and beverage enterprises (MSMEs) in Bandar Lampung City. Using quantitative methods and a sample of 100 MSMEs, the study finds that while there is a positive but insignificant relationship between green product innovation and sustainable business performance, there is a significant positive relationship between green process innovation and sustainable business performance. This suggests that MSMEs in the food and beverage sector are increasingly adopting environmentally friendly practices, such as waste management and energy conservation, leading to improved business sustainability. The study underscores the importance of integrating green innovation into business strategies to enhance performance and promote environmental responsibility.